Case Series Investigating the Efficacy and Safety of Bilateral Fluocinolone Acetonide (ILUVIEN®) in Patients with Diabetic Macular Edema: 10 Eyes with 12 Months Follow-up. Issue 1 (June 2016) - Elaraoud, Ibrahim; Quhill, Hibba; Quhill, Fahd
Abstract Introduction This short case series presents the results from 5 patients with bilateral chronic diabetic macular edema (DME), 12 months after they were initially treated with ILUVIEN® [0.2 μg/day fluocinolone acetonide (FAc)]. Methods Ten eyes from five patients with pseudophakic lenses were investigated. Patients had bilateral, chronic DME and had received prior laser and anti-VEGF therapy. Visual and anatomic outcomes were investigated 12 months post-FAc implant in both eyes. Results At baseline, central retinal thickness (CRT) was 645.3 ± 176.1 microns (mean ± standard deviation), intraocular pressure (IOP) was 13.7 ± 3.6 mmHg and visual acuity (VA) was 44.5 ± 18.6 Early Treatment Diabetic Retinopathy Study (ETDRS) letters. Mean CRT improved at 6 months (341.7 ± 169.7 microns) and 12 months (287.4 ± 103.1 microns) and there were concurrent improvements in VA (ETDRS letters were 56 ± 16 and 55 ± 16 at 6 and 12 months, respectively). Mean IOP was stable throughout and ≤21 mmHg. Left and right eyes were compared in the 5 patients by plotting changes in CFT, IOP and VA at 12 months, from baseline levels. Conclusion This bilateral case series demonstrates the effectiveness of a sustained, controlled low dose of FAc in the management of bilateral DME over a 12-month period. The FAc implant has shown to work well in treatment of bilateral DME, although longer follow-up of these patients is still needed. Funding Publication charges were funded by Alimera Sciences Ltd.